Nocturnal enuresis in children in the mountain and coastal area - T. Erna Lisma; Ani Ariani; Tiangsa Sembiring; Rafita Ramayati; Rusdidjas Rusdidjas (Paediatrica Indonesiana, 1999)
This study was designed to asses whether there is the difference ofprevalence nocturnal enuresis of children living m the moun tam and coastal area, the role of socioeconomic status and nocturnal enuresis and attitude of parent concerning to enuretic children. The cross sectional study was conducted from September to October 1995 in Brastagi (mountain area) and Pantai Cermin (coastal area). Sample was taken by simple random sampling method from children with age of 5 to 15 year.Data were collected by filling the questionnaires, physical and urine examination. Nocturnal enuresis were found 19.27% of 578 children in Brastagi and 18.46% of 547 children in Pantai Cermin, it was not significant difference statistically (p>O.OS). In age group of 5 to 6 years enuresis were the highest percentage namely 30.26% in Brastagi and 30.01% in Pantai Cermin. Poor social economic status of nocturnal enuretic children family 57.02% in Brastagi and 50.50% in Pantai Cermin, it was notsignificant difference (p>O.OS). Only 55.36% of the parents concern with enuresis on their children, while in Pantai Cermin 23.95%. In this study, we did not find the correlation between geography, poor social economic status with nocturnal enuresis and mostly of the parents considered that enuresis was not a problem.